The Emergence of Multiple-Text Manuscripts - Bausi, Alessandro; Friedrich, Michael; Maniaci, Marilena (Studies in Manuscript Cultures, 2020)
Selecting and excerpting, summarizing and canonizing, arranging texts and visual signs in manuscripts appear to be universal practices. This volume analyses the fascinating vicissitudes of birth and development, growth and decrease, of manuscripts consisting of more texts ('multiple-text manuscripts'), at the example of a vast array of manuscript cultures, from the Indian, African, Christian, Islamic, and European domains.